The effect of music therapy during shockwave lithotripsy on patient relaxation, anxiety, and pain perception. (2nd January 2016) - Akbas, Alpaslan; Gulpinar, Murat Tolga; Sancak, Eyup Burak; Karakan, Tolga; Demirbas, Arif; Utangac, Mehmet Mazhar; Dede, Onur; Sancaktutar, Ahmet A.; Simsek, Tuncer; Sahin, Basak; Resorlu, Berkan
Abstract: Objectives : To research the effect of listening to music during shock wave lithotripsy (SWL) on the patient's pain control, anxiety levels, and satisfaction. Patients and methods : The study comprised 400 patients from three hospitals. Half of patients listened to music during their first SWL session but not during their second session. The other half had no music for the first session but the second session was accompanied by music. During all sessions, with and without music, pulse rates, blood pressure, State-Trait Anxiety Inventory-State Anxiety scores (STAI-SA), Visual Analog Scale (VAS scores for pain), willingness to repeat procedure (0 = never to 4 happily), and patient satisfaction rates (0 = poor to 4 = excellent) were assessed. Results : There was no statistical difference between the two groups in terms of blood pressure and pulse rates. In both groups, the STAI-SA and VAS pain scores were lower in the session when music was listened to ( p < 0.001). The patients requested more SWL treatment be completed while listening to music and their satisfaction was greater. Conclusion : Music lowered the anxiety and pain scores of patients during SWL and provided greater satisfaction with treatment. Completing this procedure while the patient listens to music increases patient compliance greatly and reduces analgesic requirements.